PERAN SISTEM INFORMASI AKUNTANSI DALAM PENYUSUNAN DAN PELAKSANAAN ANGGARAN - Putri, Nurapni Jami (LPPM Universitas Bina Bangsa, 2024)
This research focuses on how the role of accounting information systems (SIA) can increase effectiveness and efficiency in the process of preparing and implementing the budget at the Sungai TFull City Food Security Office. This research started from common problems that are often faced by government agencies, namely lack of accuracy and delay in preparing budgets, as well as lack of transparency in its implementation. By utilizing the Accounting Information System, it is hoped that a more integrated and structured working mechanism can be created, so that financial information can be managed better. This study proposes a qualitative descriptive research method, which involves collecting data through observation and interviews with employees of the Sungai TFull City Food Security Office. The results of this study show the role of the Accounting Information System (SIA) in the preparation and implementation of the budget at the Sungai TFull City Food Security Office